Lignocaine metabolite formation: an indicator for liver dysfunction and predictor of survival in surgical intensive care patients - Schröter, Jens; Wandel, Christoph; Böhrer, Hubert; Schmidt, Heinfried; Böttiger, Bernd W.; Martin, Eike (Anaesthesia, 1995)
Formation of the lignocaine metabolite monoethyl-glycine-xylidide (MEGX) by hepatic cytochrome P450 enzymes is a new method for evaluating liver function. The purpose of this study was to compare MEGX formation with other liver function parameters in surgical intensive care unit patients. The study included 29 critically ill patients who had been admitted to the unit for more than 3 days with a median APACHE III score-predicted mortality > 30%. On day 4, lignocaine was given intravenously at a dose of 1 mg.kg-1 over 2 min and MEGX formation was measured 15 min later. Eighty-nine percent of the patients had MEGX values below 90μg.l-1 indicating impaired liver function. Eleven patients died, 18 patients survived. The group of patients with fatal outcome had significantly lower MEGX values (median: 23μg.l-1) than the group of survivors (median: 53μg.l-1, p < 0.01). Bilirubin values were elevated in the non-survivor group (median: 2.8mg.dl-1) compared to the survivors (median: 0.9mg.dl-1, p < 0.05). There was no significant difference between the two groups in the other liver function tests. We conclude from our results that the MEGX test can be considered an indicator for hepatic dysfunction and predictor of survival in critically ill patients.